Social scientific-research on the Troubles in Northern Ireland - the problem of objectivity - Taylor, R (Economic & Social Studies, 1988)
The growth in output of social scientific research on Northern Ireland and on the `Troubles? is described. Despite a considerable body of work the research on the `Troubles? encounters distinct problems concerning objectivity. This is drawn out in terms of the State's relationship to social scientific research and the predicament facing individual academic researchers. The problems are shown to lie in the lack of consensus for State legitimacy.
Keywords: Politics and government - Northern Ireland; Northern Ireland - Troubles